2018
DOI: 10.1186/s40066-018-0222-0
|View full text |Cite
|
Sign up to set email alerts
|

GIS modeling of potentially suitable sites for aquaculture development in the Lake Tana basin, Northwest Ethiopia

Abstract: Background: Small-scale pond aquaculture has been practiced in various parts of the Lake Tana basin. However, its establishment and expansion have been carried out regardless of the suitability of the locations in terms of land, water, socioeconomic and other inputs available to the aquaculture development. In recent years, there is also an increased demand for aquaculture product, and the government and other private institutions have given much attention to the sector. In response to this need, it is necessa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 27 publications
(33 reference statements)
0
26
0
Order By: Relevance
“…The key advantages of MCE techniques are that they are well established for aquaculture zoning, they can combine multiple criteria (many more than those used in this study; [19,20,55]), and may develop models under different hierarchies, priorities, and scenarios [8]. However, the main problem in the analysis of land suitability for aquaculture in ponds dug in the soil, and in general for any activity, lies in the lack of spatial data of the criteria [16].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The key advantages of MCE techniques are that they are well established for aquaculture zoning, they can combine multiple criteria (many more than those used in this study; [19,20,55]), and may develop models under different hierarchies, priorities, and scenarios [8]. However, the main problem in the analysis of land suitability for aquaculture in ponds dug in the soil, and in general for any activity, lies in the lack of spatial data of the criteria [16].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this being stated, no such approach was applied, because it depends on the georeferenced locations of the fish farms, and even though SDM such as MaxEnt has an extremely small sample size tolerance [69], it was considered inappropriate to use only the five farms, as it could affect the performance of the model. For further studies, the additional confidence that a combined approach to MCE and SDM would bring would be of vital importance The key advantages of MCE techniques are that they are well established for aquaculture zoning, they can combine multiple criteria (many more than those used in this study; [19,20,55]), and may develop models under different hierarchies, priorities, and scenarios [8]. However, the main problem in the analysis of land suitability for aquaculture in ponds dug in the soil, and in general for any activity, lies in the lack of spatial data of the criteria [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we performed a literature review on frequently used criteria for aquaculture operation and siting. While most studies showed a clear focus on environmental criteria, some also incorporated social and economic parameters [34][35][36][37].…”
Section: Identification Of Requirements and Limitations For Trout Pro...mentioning
confidence: 99%